1995
DOI: 10.1139/v95-044
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of near-infrared absorbing pigments. II. Structure determination of aceanthrene green and derivatives

Abstract: Abstract:The reported structure of aceanthrene green, a pigment prepared by potassium hydroxide fusion of 1.9-anthracenedicarboxylic imide, was found to be incorrect. The structure of the pigment is reassigned to 7,8,15,16-dibenzo[a j]perylenetetracarboxylic diimide on the basis of COSY, NOESY, and inversion-recovery 'H NMR experiments. N-Alkyl-or N-phenyl-l,9-anthracenedicarboxylic imides, aceanthryleno[l,2-blquinoxaline, and a benzimidazole derivative of 1,9-anthracenedicarboxylic anhydride were found to giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…This ratio is higher than that reported in a previous investigation in which 6 a was the starting material. [15] Only 7 was detected in the reaction of N-alkylated or N-arylated derivatives of 6 with the alkali melt (monitored by TLC and NMR spectroscopy), in accordance with the earlier investigation. [15] .…”
Section: Wwwchemeurjorgsupporting
confidence: 89%
See 2 more Smart Citations
“…This ratio is higher than that reported in a previous investigation in which 6 a was the starting material. [15] Only 7 was detected in the reaction of N-alkylated or N-arylated derivatives of 6 with the alkali melt (monitored by TLC and NMR spectroscopy), in accordance with the earlier investigation. [15] .…”
Section: Wwwchemeurjorgsupporting
confidence: 89%
“…[15] Only 7 was detected in the reaction of N-alkylated or N-arylated derivatives of 6 with the alkali melt (monitored by TLC and NMR spectroscopy), in accordance with the earlier investigation. [15] . The alkali-induced coupling of 6 results first in the formation of a red vat of the green vat dye 7 and is thus completely different from the formation of other carboxyimides, such as perylenetetracarboxydiimides.…”
Section: Wwwchemeurjorgsupporting
confidence: 89%
See 1 more Smart Citation
“…The hexabromide 10 possesses an enhanced solubility relative to 1 c, but a lower photochemical stability. It was found that only bromides closest to the imide positions (1,6,11,16) were substituted with the phenoxy groups upon phenoxylation. The two "inner" bromides remained even after the long reaction times and drastic conditions.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Benzannulation in the "bay"-region of rylenes with the introduction of anthracene (2, l max = 701 nm) or tetracene (3, l max = 1018 nm) elements resulted in significant bathochromic shifts of the absorption maximum, presumably due to the nonplanarity of the molecules formed. [11][12][13] The absorption of dibenzoperylenebis(dicarboximide) [11] 2 and dibenzopentarylenebis(dicarboximide) [13] 3 was shifted by about 180 nm relative to the perylene 1 a (l max = 524 nm) and pentarylene 1 d (l max = 830 nm) derivatives, respectively. [10] However, enlargement of the p system did not always promote a shift to longer wavelengths.…”
mentioning
confidence: 99%